INNOVATIVE TECHNOLOGIES FOR THE FINANCING OF THE SOCIAL DEVELOPMENT OF THE NATIONAL ECONOMY - Golovnya, O. M. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2019)
The aim of the study is to evaluate innovative technologies for social development financing. Research methods. Theoretical and methodological basis of the research is the scientific work of domestic and foreign authors on financing of social development with the help of innovative technologies, Internet resources. The study uses a set of general and special scientific methods and approaches, including: monographic - for the literary review of the problem under study; systemic and structural analysis – for interpretation of the essence of fundraising, crowdsourcing, crowdfunding as complex economic categories, logical generalization, systematic method, method of comparisons, graphical methods, which allowed to ensure the conceptual unity of the research. Results of work. Innovative technologies of financing of social development are analyzed, among them: fundraising, crowdsourcing, crowdfunding. The activities of the Na-Starte Kraudfanding Platform, including the involvement of interested parties in this Crowdfunding Platform, are described. It has been established that financing of social projects by providing grants is a significant step forward from the point of view of development of social responsibility of business. It is traced that today in Ukraine there are a number of active grant programs in the field of education, science, medicine, and social security. Conclusions. The listed innovative approaches become relevant in the context of decentralization and community development, in particular, participatory budgeting is the ability of male and female residents of the city to participate in deciding how to distribute a certain part of the budget.